Comparative Analysis of Operational and Investment Costs Between Diesel Trucks and Electric Trucks in Coal Transportation Activities in West Kutai Regency - Roni Roni; Mentiana Sibarani (Eduvest - Journal of Universal Studies, 2025)
This study aims to compare investment and operational costs between electric trucks (Electric Vehicles/EV) and diesel trucks (Internal Combustion Engine/ICE) in coal transportation activities in Kutai Barat Regency. The main issue addressed is the high investment cost of electric vehicles and their suboptimal operational productivity compared to conventional vehicles. A employed using descriptive statistics and the non-parametric Mann–Whitney U test. Data were collected from actual operational measurements of both vehicle types. The results show that electric trucks have significantly higher investment costs than diesel trucks. However, in terms of energy efficiency, electric trucks offer significant savings up to 72.9% in energy costs. Meanwhile, operational and total costs between the two truck types were not statistically different. In terms of productivity and daily output capacity, diesel trucks were significantly superior. These findings suggest the adoption of a mixed-fleet strategy and underscore the importance of developing supporting infrastructure such as swab charging stations to optimize the role of electric vehicles in the mining sector.